2020
DOI: 10.2174/1871527318666191114093749
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 Fatty Acids as Druggable Therapeutics for Neurodegenerative Disorders

Abstract: : Neurodegenerative disorders are commonly associated with a complex pattern of pathophysiological hallmarks, including increased oxidative stress and neuroinflammation, which makes their treatment challenging. Omega-3 Fatty Acids (O3FA) are natural products with reported neuroprotective, anti-inflammatory, and antioxidant effects. These effects have been attributed to their incorporation into neuronal membranes or through the activation of intracellular or recently discovered cell-surface receptors (i.e., Fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 202 publications
0
13
0
Order By: Relevance
“…Specifically, it has been demonstrated that n-3 fatty acid supplementation is able to improve AD-associated brain pathology in several transgenic mouse models of AD, including 5xFAD mice, to reduce amyloid plaque burden and to improve learning and memory [ 44 , 45 , 115 - 117 ]. The majority of the beneficial properties of PUFAs have been attributed to their reported neuroprotective, anti-inflammatory, and antioxidant effects [ 118 ] and specifically to their capability to change the composition of cell membranes, replacing cholesterol and promoting the non-amyloidogenic pathway of APP processing, thus decreasing the Aβ burden. Herein, we identify a previously unknown effect of n-3FAs on cellular proteostasis, namely through the conformational activation of the proteasome.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, it has been demonstrated that n-3 fatty acid supplementation is able to improve AD-associated brain pathology in several transgenic mouse models of AD, including 5xFAD mice, to reduce amyloid plaque burden and to improve learning and memory [ 44 , 45 , 115 - 117 ]. The majority of the beneficial properties of PUFAs have been attributed to their reported neuroprotective, anti-inflammatory, and antioxidant effects [ 118 ] and specifically to their capability to change the composition of cell membranes, replacing cholesterol and promoting the non-amyloidogenic pathway of APP processing, thus decreasing the Aβ burden. Herein, we identify a previously unknown effect of n-3FAs on cellular proteostasis, namely through the conformational activation of the proteasome.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of omega-3 polyunsaturated fatty acids (PUFA) on fighting inflammation and oxidative stress are well stablished in literature ( 1 , 2 ). Docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA), mainly, have been shown to have neuroprotective abilities through both vascular and neuronal mechanisms ( 3 , 4 ), being associated with reduced white matter hyperintensities (WMH) accumulation and delayed neurodegeneration ( 5 , 6 ). In this sense, trials based on omega-3 PUFA supplementation have been developed.…”
Section: Single-nutrient Approachesmentioning
confidence: 99%
“…Chemical small molecules (CSMs) represent a big class of drugs which mainly function by binding with disease related target molecules [2]. Given the huge space of target molecules and CSMs, evaluating the druggable potential of both targets [3][4][5][6] and CSMs [7][8][9][10][11] is thus one of the hearts of drug discovery. For CSMs, it is known that a number of drug related properties (druggable properties) affect their druggable potential, for example human intestinal absorption, blood-brain barrier penetration [12], and some pharmacokinetic properties [13].…”
Section: Introductionmentioning
confidence: 99%